Simultaneous copper migration and removal from soil and water using a three-chamber microbial fuel cell - Zhang, Jingran (Environmental technology, 2021)
In this study, we constructed a three-chamber microbial fuel cell (TC-MFC) that avoided the adverse effects of H+ diffusion on anode microorganisms in the acidic catholyte and the precipitation of heavy metals in the soil near the cathode side (S4), while also achieving migration of copper from the soil and reduction of Cu2+ in the catholyte. The removal efficiency of acid-soluble Cu from the soil near the anode region reached 42.5% after 63 days of operation at an external resistance of 100 Ω and electrode spacing of 10 cm, and Cu2+ in the catholyte was completely removed within 21 days. Heavy metal mobility index (MF) values indicated that the bioavailability and mobility of heavy metals were reduced by the TC-MFC. We found that changing the cathode potential and external circuit current in TC-MFC would affect the type (via XRD) and morphology (via SEM) of cathode deposits and the average removal rate of heavy metals. At the meantime, it should be noted that the interaction between the electric-field-dependent soil heavy metal migration and electron-dependent copper reduction in TC-MFC occurred, which was confirmed to have a relationship with the negative correlation between voltage and current during the test